2022
DOI: 10.52731/lir.v002.052
|View full text |Cite
|
Sign up to set email alerts
|

Combining Key Performance Indicators and Signs of Changes in Students to improve the quality of education in Institutional Research based on Eduinformatics

Abstract: In recent years, most Japanese universities have started to operate departments of institutional research (IR). In IR fields, Key Performance Indicator (KPI) is important to evaluate the quality of education. Eduinformatics, a novel interdisciplinary field proposed by us, provides good analyses that will help us to solve educational problems. This paper emphasizes that we have to consider whether the evaluation of KPIs is the best method to check the quality of education in universities. We discuss the problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The differences between the standard values could be influenced by learners' over-or underestimation. For example, [26], who investigated changes in learners' self-esteem in certain lectures, has suggested that the learners were affected positive bias [27] or negative bias [28]. It is difficult to discuss this hypothesis from the limited number of participants, but we should have this perspective for future analysis.…”
Section: Grouping Of the Participantsmentioning
confidence: 99%
“…The differences between the standard values could be influenced by learners' over-or underestimation. For example, [26], who investigated changes in learners' self-esteem in certain lectures, has suggested that the learners were affected positive bias [27] or negative bias [28]. It is difficult to discuss this hypothesis from the limited number of participants, but we should have this perspective for future analysis.…”
Section: Grouping Of the Participantsmentioning
confidence: 99%